STATIC BEHAVIOUR OF COMPOSITE BARS WITH THE MATRIX MADE FROM AMBRESIT - Cosmin Mihai MIRITOIU; Daniela Florentina TARATA; Alexandru BOLCU; Claudia Alina IOVAN; Ovidiu STOIAN (Fiabilitate şi Durabilitate)
In this paper, I have built a composite sample made from glass fiber as reinforcement and Aropol as matrix. For this sample, I have used an experimental procedure to determine the damping properties and the frequency of the first eigenmode. The experimental process is characterized by clamping the bar at one end and leaving it free at the other. At the free end, I have placed an accelerometer to record the bar free vibrations. I have applied an initial force, then I have removed the force and left the sample to vibrate without any other restrictions. From these vibrations I have determined the damping factor and the eigenfrequency.